Membangun Budaya Hukum Masyarakat Penegak Hukum dalam Pemberantasan Tindak Pidana Narkotika - Zainab Ompu Jainah (Universitas Bandar Lampung (UBL), 2011)
This study is about a building legal culture of law enforcement apparatur for narcoticcrime (The birth studies Institute of the National Narcotics Agency). Efforts to reformthe criminal law in the prevention and eradicate of narcotic drugs should be increasedconsidering the extra-ordinary-crime by using policies that not only the use of criminalenforcement but also must be integrated with the use of means-beyond the means ofcriminal law (non-penal), one of which is the law of cultural development of nationalNarcotics Board. The legal culture of the institution through good performance,consistency, and the consequent increase in human resources, as well as goodmanagement which always be able to provide evidence that their presence actuallymeet the goals of criminal law reform